PENERAPAN PEMBELAJARAN FARMING GARDENING PROJECT PADA ANAK USIA DINI DI PAUD ASTER - Chofid Bachrudin (JP3M: Jurnal Pendidikan, Pembelajaran dan Pemberdayaan Masyarakat, 2019)
This research is aimed at gaining an objective picture of how the effect of teaching and learning model in developing young learners’ social and emotional behavior. The research itself was a quasi experimental in nature, in which an experimental group (those young learners who were taught using the farming gardening project) was compared to a regular (control) group (those who were taught using a conventional teaching). The research subject was the young learners of PAUD ASTER. The data for the research were collected through observation checklist, interview guide, and table and picture. The research showed that there was a significant difference of behavior between the students belonging to the experimental group and those belonging to the control group. A higher gain was shown by those belonging to those taught using the faming gardening project than those taught conventionally. Thus, it could be inferred that teaching through the farming gardening project may better develop the students’ social and emotional behavior.